RESISTANCE PREDICTION OF SOLAR BOAT IN CALM WATER USING COMPUTATIONAL FLUID DYNAMIC APPROACH - Nur Ain, A.R; Muhamad Daniel Haiqal; Mohd Azahari, J; Khairuddin, N.M.; Norhanifah, A.R; N. Manap (Marine Frontier, 2023)
This project presents a CFD simulation on a swath solar boat. Swath is a Small Waterplane Area Twin Hull. It is a hull design that has a small waterplane area with pontoons. Researching the hull for the resistance and pressure distribution analysis takes too much time and money. One way to solve this is by implementing CFD in Boat development. Computer Fluid Dynamics, CFD is a simulation to replicate real-world data. It starts by developing the boat's model and setting up the boundary conditions around it. The boundary will be mesh and transferred into CFD, followed by setting up the code solver and running the simulation. Next, the resistance and hull distribution can be generated. In this project, it is found that the higher the speed, the higher the resistance. Pressure distribution at a slow speed is concentrated below the pontoons, but when the speed increases, the pressure is more concentrated in front of the pontoons and struts. This project is expected to give a significant improvement in ship development.